CXCR2 increases in ALS cortical neurons and its inhibition prevents motor neuron degeneration in vitro and improves neuromuscular function in SOD1G93A mice - Valentina La Cognata (Elsevier, 2021)
Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disease characterized by depletion of motor neurons (MNs), for which effective medical treatments are still required. Previous transcriptomic analysis revealed the up-regulation of C-X-C motif chemokine receptor 2 (CXCR2)-mRNA in a subset of sporadic ALS patients and SOD1G93A mice. Here, we confirmed the increase of CXCR2 in human ALS cortex, and showed that CXCR2 is mainly localized in cell bodies and axons of cortical neurons. We also investigated the effects of reparixin, an allosteric inhibitor of CXCR2, in degenerating human iPSC-derived MNs and SOD1G93A mice. In vitro, reparixin rescued MNs from apoptotic cell death, preserving neuronal morphology, mitochondrial membrane potential and cytoplasmic membrane integrity, whereas in vivo it improved neuromuscular function of SOD1G93A mice. Altogether, these data suggest a role for CXCR2 in ALS pathology and support its pharmacological inhibition as a candidate therapeutic strategy against ALS at least in a specific subgroup of patients.